Implementing STAD To Improve Students’ Ability Of STIKOM Tunas Bangsa In Writing Narrative Text - Fitri Rizki; Rizky Khairunnisa Sormin; Ika Purnama Sari (English Lecturers and Teachers Association (ELTA), 2023)
This research was conducted to increase students’ writing ability by using the Students Team Achievement Division (STAD) Technique. The researcher wanted to find out whether or not Students Team Achievement Division (STAD) Technique can increase the students’ writing skill and to analyze the classroom situation when the Students Team Achievement Division (STAD) Technique is implemented in writing class. The population of the research was the first semester students STIKOM Tunas Bangsa Pematang Siantar. This research used Classroom Action Research (CAR) and composed for two or more cycles then it observed and evaluated to identify all facts including the success and the failure of the action. It means that the action should be stopped or continued and revised to the next cycle based on the selected criteria of success. After the implementation of Students Team Achievement Division (STAD) Technique in every cycle, the students’ writing score were getting better. The result of student can be seen from the result of students’ average score by their writing. The first Cycle was 44.00 and the second Cycle was 77.00. After the implementation the students get better score. It can be concluded that Students Team Achievement Division (STAD) Technique can increase their ability in writing narrative text. Keywords: Students Team Achievement Division (STAD); Writing; CAR